Comparative study of high velocity impact response of aluminium 3105-H18 and carbon fibre-epoxy composite double hat bumper beams. (2021) - Salifu, Smith; Desai, Dawood; Ogunbiyi, Olugbenga; Sadiku, Rotimi; Adesina, Oluwagbenga; Adesina, Olanrewaju
Abstract: The quest to reduce the energy consumption in automotive has resulted in the development and use of lightweight materials for the design of vehicles. Also, stiffer legislation is being put in place to enforce the utilization of lightweight components for vehicles in order to guarantee the safety of both pedestrians and passengers. Hence, the bumper beams of a vehicle which is a major contributor to its total weight must be made of lightweight materials capable of absorbing kinetic energy developed during a collision. In this paper, the impact response of a double hat bumper beam made with two different materials, aluminium Al (3105-H18) and carbon fibre-epoxy composite and subjected to a high-velocity impact was simulated using finite element analysis code, Abaqus CAE/2019. The response of both materials was compared, and the results show that carbon fibre-epoxy composite absorbed equal amount of energy as aluminium during collision and thus, can be used as a bumper beam for vehicles.